The epidemiology of myocardial infarction. Trends in incidence, risk factors, severity, treatment and outcomes of myocardial infarction in a general population. - Mannsverk, Jan Torbjørn (Circulation, 2019)
Paper 1 and 2 were based on the Tromsø Study, a population-based, prospective cohort study with repeated screenings for cardiovascular risk factors and follow-up with regard to disease incidence and mortality. Paper 3 was based on a local registry of consecutively patients with presumed ST-elevation myocardial infarction who had been given prehospital thrombolytic therapy, and then admitted to the University Hospital in Tromsø. In paper 1, we showed that a substantial part of the decline in coronary heart disease mortality in the young and middle-aged population was due to a decreased incidence of myocardial infarction. The study indicates that the population burden of coronary heart disease may be shifting towards women and elderly patients, suggesting that preventive gains have not penetrated equally throughout the population. The severity and case fatality of the disease, however, was declining in all groups. In paper 2, we found that age- and sex-adjusted incidence of total coronary heart disease decreased by 3% annually over 15 years of follow-up. The decrease was found primarily in reductions in out-of-hospital sudden cardiac death and hospitalized ST-elevation myocardial infarction. Reductions in serum cholesterol accounted for approximately one-third of the event decline, but decreases in smoking, blood pressure, and heart rate and increased physical activity all contributed. Increases in body mass index and diabetes mellitus were associated with modest increases in disease outcomes. Overall, risk factors accounted for 66% of the decline in incidence. Furthermore, the decline in event rates and the decline in case fatality each explained 50% of the decline in coronary heart disease mortality. This was partly explained by less severe disease in those afflicted, but also by a major improvement in treatment. In paper 3, we showed that ambulance clinicians with the support of hospital cardiologists could safely and effectively perform prehospital thrombolytic therapy. The implementation of this system was ...